Ecologia e evolução da dispersão de sementes por primatas neotropicais - Lisieux Franco Fuzessy (2017)
The mutualism among fleshy fruits and fruit-eating vertebrates largely influence tropical forests functioning and dynamics, and promotes fundamental evolutionary and ecological consequences. During food handling, frugivores transport seeds to sutable sites to germinate and grow and, in turn, plants offer a nutritional reward. Thus, the frugivorefeeding ecology and activity patterns determine its effectiveness as a disperser. Seed dispersal process establishes the probability of seed and seedling survival, seed germination and seedling recruitment. These impacts of mutualistic interactions on plant reproduction and fitness therefore influence selection and evolution of fruit traits. Primates,toghether with birds and bats, are the main disperser agents in tropical forests. A large body size associated with the arboreal habit and high fruit consumption are the outcome of sensorial, morphological and locomotor daptations, which reflects in feeding guilds. Here we gather, organize and expand available information about the ecological and evolutionary consequences of seed dispersal by primates in the Neotropical region aiming to fill knowledge gaps. We evaluate, from a plant ecological and phylogenetic point of view, the consequences of mutualistic interactions with Neotropical primates. We tested hypotheses on the ecology and evolution of seed dispersal by distinct feeding guilds. In terms of feeding ecology primates tend to be generalist and this fact prevented us to identify the consequences of mutualism to the evolution of fruit morphology. However, the strong association among morphological fruit traits in primate-dispersed species pointed to the existence of a dispersal syndrome. Also, we showed that primates are able to swallowand disperse a wide range of plant species, fruit colors, types and sizes, and move seeds to sites far from the zone of influence of the parent crown, and also promote germination after gut passage. The role of primates as seed dispersers is defined according to the feedingguilds, and the degree of frugivory modulates the quality of the service offered